Reinstatement of Persicaria sinica Migo (Polygonaceae, Persicarieae) - Li, Bo (Phytotaxa, 2014)
Persicaria sinica (≡ Polygonum sinicum) was considered as a synonym of Polygonum thunbergii (≡ Persicaria thunbergii), and its specimens were frequently identified as the latter, or occasionally as Polygonum dissitiflorum (≡ Persicaria dissitiflora). However, a detailed analysis of the type materials and additional specimens clearly indicates that P. sinica is a distinct species, which can be easily distinguished from P. thunbergii and P. dissitiflora, as well as other species of Persicaria section Echinocaulon (≡ Polygonum section Echinocaulon) by habit, the shape of the leaf blade, the apex of the ocreae, the structure of the inflorescences, the indumentum and color of the peduncles, and the shape and surface of the achenes. The specific status of P. sinica is thus reinstated. Additionally, complete taxonomic description, geographic distribution, ecological observations, and a key to distinguish the related species are also provided.